Tuning phosphorescence features of triphenylamines by varying functional groups and intermolecular interactions - Goudappagouda; Asokan, Kiran; Nayak, Rashmi; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Dyes and Pigments, 2020)
Organic room temperature phosphorescent materials are known for their synthetic feasibility, tunable phosphorescence wavelength and lifetime, etc. Hence new design strategies have been applied on various fluorophores to improve phosphorescence features. Among those, triphenylamines are phosphorescence active due to the presence of nitrogen atom, propeller molecular structure, and intermolecular interactions in the crystal state. Here we have studied the room temperature phosphorescence of a series of triphenylamines with various functional groups. Detailed studies have shown that the phosphorescence can be fine-tuned by functional group modification. A long phosphorescence lifetime around 100 ms at room temperature in air can be achieved by the interplay of intermolecular interactions, singlet-triplet energy gap and extent of intersystem crossing using functional group variation. Interestingly, an exciplex assisted ultralong phosphorescence lifetime (more than 20 times) is observed for a combination of triphenylamine and naphthalenemonoimide in air.
Keywords: Exciplex; fluorescence; Phosphorescence; triphenylamine

Thermally activated delayed fluorescent solvent-free organic liquid hybrids for tunable emission applications - Nidhankar, Aakash D. D.; Goudappagouda; Kothavade, Premkumar D.; Dongre, Sangram D.; Veer, Sairam Dnyaneshwar; Dash, Soumya Ranjan; Rajeev, Kavya; Unni, K. N. Narayanan; Shanmuganathan, Kadhiravan; Babu, Sukumaran Santhosh (Chemistry-An Asian Journal, 2023)
The synthetic feasibility and excellent luminescence features of organic molecules attracted much attention and were eventually found useful in lighting applications. In this context, a solvent-free organic liquid having attractive thermally activated delayed fluorescence features in bulk along with high processability has prime importance. Herein, we report a series of naphthalene monoimide-based solvent-free organic liquids exhibiting cyan to red thermally activated delayed fluorescence with luminescence quantum yields up to 80% and lifetimes between 10 to 45 mu s. An effective approach explored energy transfer between liquid donors with various emitters exhibiting tunable emission colors, including white. The high processability of liquid emitters improved the compatibility with polylactic acid and was used for developing multicolor emissive objects using 3D printing. Our demonstration of the thermally activated delayed fluorescence liquid will be much appreciated as a processable alternate emissive material suitable for large-area lighting, display, and related applications.
Keywords: 3D printing; Energy Transfer; OLED; Organic Liquids; TADF

Tailoring helical ends of π-extended [6]heterohelicenes to control optical, and electrochemical features - Kumar, Viksit; Dongre, Sangram D.; Venugopal, Geethu; Narayanan, Aswini; Babu, Sukumaran Santhosh (Chemical Communications, 2024)
The inherent helical chirality and improved pi-stacking capabilities endow helicenes with fascinating photophysical characteristics when decorated with lateral pi-extensions. Here, we report the synthesis and physicochemical characterization of expanded hetero[6]helicenes fused with thiadiazole and selenadiazole rings at the helical ends. Comparing these heterohelicenes revealed the impact of the heteroatom-embedded aromatic rings on the excited state and redox features. A small structural variation of the terminal rings from thiadiazole to selenadiazole caused a striking change in the heterohelical nanographenes. The inherent helical chirality and improved pi-stacking capabilities endow helicenes with fascinating photophysical characteristics when decorated with heteroatoms.